Sustainability communication across Asia fundamental principles, digital strategies and community engagement - Saleh, Mohamad Saifudin; Rahman, Nur Atikah A; Kasuma, Shaidatul Akma Adi (Routledge, 2023)
Sustainability Communication across Asia distils the core components of environmental communication in the diverse milieu of Asian nations such as Indonesia, Malaysia, the Philippines, Thailand and China. The chapters in this book engage readers in a clear-sighted view of issues, challenges and strategies related to sustainability communication in Asia, examining fundamental principles, digital strategies and the role of language, as well as community engagement. The first part of the book features underpinning ideologies of sustainability communication. The authors go on to explore the prevalent trends and approaches of sustainable communication in the digital realm, examining the internet in general, social media and gaming platforms. Finally, the book discusses the green efforts adopted among selected Asian communities, the role of communication and the resulting societal impacts. Readers will be introduced to many related examples of Asian sustainability cases and issues that may differ from that of the Western experiences. Interesting topics such as environmental gamification, edutainment and sustainability communication, and social media and sustainability are among those presented and elaborated in length by twenty-one writers with industrial and academic backgrounds. Practical and inspiring, this book will be of great interest to students and scholars of sustainability and environmental communication, and Asian studies in general"-- Provided by publisher.